Some Feedback about the Current National Curriculum - Malikova, Nargiza Bakhtiyorovna (International Journal on Orange Technologies, 2022)
In this article, the introduction of the National Curriculum, the advantages and conveniences of the curriculum, work on dictionaries in the textbooks "Mother Tongue and Reading Literacy", methods of working on the dictionary, the importance of speech development in school one of the tasks is to work on this vocabulary and to manage the process of enriching students ’vocabulary.